DECISION OF UNCLEAR SYSTEMS LINEAR EQUALIZATIONS OF ALGEBRA IN TENSOR BASE BY FACILITIES OF PMM MATLAb - Мінаєв, Ю. М.; Філімонова, О. Ю.; Мінаєва, Ю. І.; Гончарова, Є. О. (Science-based technologies, 2010)
The questions of deciding the fuzzy single-line algebraic equation systems by presentations of fuzzy parametersmodels (matrix of factors, right parts) by tensors 2 ranks are Considerered .Shown possibility of deciding a givenclass of problems at a rate of crisp block systems of single-line algebraic equations where factors matrixesand right parts present itself matrixes of tensors by dimensionality 3 x h 3. Example of deciding is bring.